2017
DOI: 10.1161/atvbaha.116.307787
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mas1 Receptor-Mediated Signaling in the Vascular Endothelium

Abstract: Objective Angiotensin II (AngII) has been shown to regulate angiogenesis and at high pathophysiological doses to cause vasoconstriction through the AngII receptor type 1 (AT1R). Angiotensin 1-7 (Ang-(1-7)) acting through the Mas1 receptor can act antagonistically to high pathophysiological levels of AngII by inducing vasodilation, while the effects of Ang-(1-7) signaling on angiogenesis are less defined. To complicate the matter, there is growing evidence that a subpressor dose of AngII produces phenotypes sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 49 publications
3
47
0
Order By: Relevance
“…For instance, Ang-(1-7) contributes to endothelial homeostasis via ERK1/2, eNOS, PI3-kinase and Akt, all of which are also associated with AngII signaling via AT1R [4,[8][9][10]. A few relatively detailed proteomic analyses of Ang-(1-7)/Mas signaling have been performed in our laboratory and by others, and the results of those studies further support a convergence in AngII/AT1R and Ang-(1-7)/Mas signaling [3,11].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…For instance, Ang-(1-7) contributes to endothelial homeostasis via ERK1/2, eNOS, PI3-kinase and Akt, all of which are also associated with AngII signaling via AT1R [4,[8][9][10]. A few relatively detailed proteomic analyses of Ang-(1-7)/Mas signaling have been performed in our laboratory and by others, and the results of those studies further support a convergence in AngII/AT1R and Ang-(1-7)/Mas signaling [3,11].…”
Section: Introductionsupporting
confidence: 71%
“…However, recent studies reaffirm that AngII/AT1R signaling plays a key role in vascular homeostasis. For instance, renin suppression in animal models impairs angiogenesis [1] and vascular reactivity to vasodilator stimuli [2], and restoration of physiological AngII levels in models of impaired renin regulation restores vascular reactivity and endothelial function [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the death cases, persons with hypertension and /or diabetes made up the largest share, which could be explained by the fact that hypertension and diabetes top the chronic disease chart in China [27]. ACE2 is a crucial regulator of the renin-angiotensin system, and plays a regulatory role in the central regulation of blood pressure and cardiovascular function and could become an attractive target for the treatment of hypertension [28,29]. COVID-19 virus uses the receptor ACE2 to enter into target cells [30], precisely the same as SARS-CoV.…”
Section: Underlying Diseasesmentioning
confidence: 99%
“…Interestingly, AT1R activity was reduced in the amygdala of mice brains that lacked the MAS receptor, further highlighting the crosstalk among the various components of the RAS (Von Bohlen und Halbach et al, 2000). Interestingly, a subpressor dose of Ang II has a similar angiogenic response to a low dose of Ang (1-7), further highlighting the complex interplay between various components of the RAS (Hoffmann et al, 2017). Although the cannabinoid type 1 receptor has been demonstrated to potentiate AT1R profibrinogenic activity by way of heterodimerization (Rozenfeld et al, 2011), it has also has been demonstrated to diminish AT1R's ability to activate key signaling pathways in astrocytes (Haspula and Clark, 2017b).…”
Section: Classic and Nonclassic Ras And Therapeutic Interventionsmentioning
confidence: 99%